Pengembangan Usaha Kopi Nating Menjadi Ice Cream Kopi - Chabir Galib, Andi Ahmad; Ismaya, Ismaya; Sitonda, Syawal; Elihami, Elihami (LP2M Universitas Muhammadiyah Enrekang, 2024)
Ice cream is a dairy product that is made by freezing and mixing the raw ingredients together. The ingredients used are a combination of milk with additional ingredients such as sugar and honey or without flavorings and colors, and stabilizers. The ingredients for mixing ice cream are called ice cream mix (ICM), by mixing the right ingredients and processing correctly, good quality ice cream can be produced. This activity was carried out in Nating Hamlet, Bungin District, Enrenkang Regency with the aim of providing education to the people of Nating Hamlet and developing coffee processing certification. The methods used were observation, delivery of material and direct practice in making ice cream from Arabica nating coffee. It is hoped that this activity can increase the education and insight of the community in Nating Hamlet so that they can be open to seeing the potential and exploiting the potential of the surrounding nature.